Effects of Pranlukast Hydrate on Serum Eosinophil Cationic Protein Levels in Patients with Adult Bronchial Asthma - Horiguchi, Takahiko; Tachikawa, Soichi; Kasahara, Junichi; Doi, Masashi; Shiga, Mamoru (Arzneimittelforschung, 1999)
Pranlukast hydrate (CAS 103177-37-3, ONO-1078) was administered to 20 patients with bronchial asthma, and examined the effects of this agent on serum eosinophil cationic protein (ECP) levels and peripheral blood eosinophil counts. The mean serum ECP level in the group comprised of patients with bronchial asthma was significantly higher than that in the control group comprised of healthy adults. In responders in whom improvement in asthmatic symptoms was observed, serum ECP levels were significantly decreased compared to the pretreatment values 4 weeks after commencement of pranlukast hydrate administration. However, there were no changes in non-responders. There was no correlation between serum ECP level and peripheral blood eosinophil count before administration of pranlukast hydrate. However, there was a correlation 4 weeks after administration was started. It is suggested that pranlukast hydrate inhibits eosinophilic activity in patients with bronchial asthma.
Keywords: Bronchial asthma; CAS 103177-37-3; ONO-1078; Pranlukast hydrate, effect on eosinophil cationic protein